2014
DOI: 10.14302/issn.2324-7339.jcrhap-13-321
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of Consistent Condom Use Among HIV-positive Women In Abia State, South-East Nigeria.

Abstract: Background: The use of condoms in marriages is a complex decision. It however plays a role in prevention of HIV and other sexually transmitted infections (STIs). The problem is, what factors and conditions determine consistent condom use among HIV positive women? This study aimed at identifying determinants of consistent condom use among HIV positive women cohabiting with their partners and attending "Heart to Heart" treatment centre in Abia State University Teaching Hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 9 publications
5
13
2
Order By: Relevance
“…This study shows that 79.8% (CI: 75.3% -83.9%) of the respondents had at least one risky sexual practice within three months prior to the study. This finding is consistent with the result (81%) reported from Uganda (15) but it is higher than study reported (70.6%) from Southeast Nigeria [32]. It is also higher than previously reported results from Addis Ababa and Gondar, other parts of the country; where the magnitude of risky sex was 36.9%, and 38% respectively [13,17].…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that 79.8% (CI: 75.3% -83.9%) of the respondents had at least one risky sexual practice within three months prior to the study. This finding is consistent with the result (81%) reported from Uganda (15) but it is higher than study reported (70.6%) from Southeast Nigeria [32]. It is also higher than previously reported results from Addis Ababa and Gondar, other parts of the country; where the magnitude of risky sex was 36.9%, and 38% respectively [13,17].…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of consistent condom use in this study is higher when compared to the studies in Nigeria (45.8%) [ 38 ] (29.4%) [ 39 ]. This difference might be due to the study time in which the latter was conducted seven years ago.…”
Section: Discussioncontrasting
confidence: 74%
“…Health care professionals should focus on educating individuals who have not disclosed their HIV-positive status to their sexual partners by demonstrating the importance of such disclosure. Women who do not disclose their HIV-positive status to their sexual partners often engage in risky sexual practices such as inconsistent condom use [23]. Results from this study are concurrent with this evidence that participants who reported using a condom 100% of the time were more likely to have disclosed their HIV-positive status to a sexual partner.…”
Section: Discussionsupporting
confidence: 67%
“…Women who do not disclose their HIV-positive status to their sexual partners often engage in risky sexual practices such as inconsistent condom use [ 23 ]. Results from this study are concurrent with this evidence that participants who reported using a condom 100% of the time were more likely to have disclosed their HIV-positive status to a sexual partner.…”
Section: Discussionmentioning
confidence: 99%